The Evaluation of Exercises Compatibility Between Revised Bloom’s Taxonomy and 2013 Curriculum Reflected in English Textbook - Susan, Susandari; Warsono, Warsono; Faridi, Abdurrachman (Universitas Negeri Semarang, 2020)
This study was aimed to evaluate the English textbook which focused on exercises provided, entitled Bahasa Inggris Kelas X (2017). This research used descriptive evaluative study in which all exercises were analyzed toward Revised Bloom;s Taxonomy as well as 2013 Curriculum in order to see its compatibility. Besides, it also examined the compatibility of 2013 Curriculum toward Revised Bloom’s taxonomy.The results of the study showed that (1) The exercises found in Bahasa Inggris textbook were compatible toward Revised Bloom’s Taxonomy. Besides, the knowledge dimensions (factual, conceptual, procedural and metacognitive) were manifested in the exercises. (2) With regard to the compatibility of the exercises toward 2013 Curriculum, the exercises found in Bahasa Inggris textbook were compatible. The exercises were designed according to the Core Competence and Basic Competence mentioned in 2013 Curriculum as they were divided according to the chapter/topic they belong to. (3) In regard to the compatibility of 2013 Curriculum toward Revised Bloom’s Taxonomy, the Core Competence and Basic Competence in 2013 Curriculum were well designed in line with the Revised Bloom’s Taxonomy. It was reflected in all basic competences that were hierachically put based on the taxonomy started from the lowest into the highest level. Furthermore, the learning activities found in 2013 Curriculum were done in Higher Order Thinking Skills. (4) Although the activities designed in the exercises are following Revised Bloom’s Taxonomy and Curriculum 2013, the material used were not too suitable with the need of vocational students in which they need more special need. The results of the study are expected to give a valuable contribution that the further study can extent the study to discuss about the quiz or test provided by school or institution to be examined toward the current curriculum and Bloom’s revised tanonomy as well as the students’ special needs in order to encourage the education practitioners to design good quiz or test for the students.